The Effects Of Information And Communication Technologies (ICT) On The Teachings/ Learning Of Arabic And Islamic Studies - Sulaiman, Kamal-deen Olawale (Ar Raniry : International Journal of Islamic Studies, 2015)
Arabic and Islamic Studies are very wide to be covered extensively within the confines of classroom lessons. These confines can be broadening to cover all areas of the subjects using modern information and communication technologies to meet and stimulate the interest, appreciation and curiosities of students. This paper, therefore, intends to investigate the overall effects of ICT in the teaching/learning of Arabic and Islamic Studies for the 21st century in Nigeria. It, also, investigates the role of ICT in the teaching/learning of the two subjects and the challenges facing the teachers of the subjects. The ICT resources for teaching/learning of the subjects would also be examined. The methodology employed in this study was derived from books, journals, archives, newspapers, reports, internet and the Holy Qur’an. The paper emphasizes the importance of making schools conducive for learning and one major factor that contributes to learning process is the use of ICT. It, also, revealed that, ICT is used as a teaching aid possibly in the demonstration and discussion processes. The paper recommended that it is significantly important for the Arabic and Islamic studies teachers to understand the skills and knowledge required in the ICT era. Also, priorities for future development and acquiring of ICT knowledge is essential to Arabic and Islamic Studies teachers so as to be able to apply ICT knowledge where appropriate in their professional lives as educators, education analysts and school managers. While it concluded that the ICT has a lot of roles in the teaching/learning of Arabic and Islamic studies.